Strengthening Organizational Culture, Personality, Trust and Work Motivation in an Effort to Improve Teacher Performance - Winda Suci Lestari Nasution; Soewarto Hardhienata; Rita Retnowati (Journal of Social Research, 2024)
This study aims to improve the performance of public junior high school teachers in Purwakarta Regency by strengthening organizational culture, personality, trust, and work motivation. The research used Path Analysis and SITOREM Analysis to analyze the data. The study involved 1,831 teachers across 78 schools in 17 sub-districts. Results showed that organizational culture, personality, confidence, motivation, trust, and motivation significantly influenced teacher performance. The indicators that were maintained or developed were conscientiousness, agreeableness, emotional stability, support from superiors, teaching planning and preparation, application of teaching methods and strategies, use of learning media, and behavior in managing classes. The study also identified indicators that needed immediate improvement. The findings will be used as recommendations for teachers, principals, school supervisors, and related education offices.